INFLUENCE OF HEARING AGE AND UNDERSTANDING VERBAL INSTRUCTIONS IN CHILDREN WITH COCHLEAR IMPLANTS - Đoković, Sanja; Todorović, Selena (Specijalna edukacija i rehabilitacija, 2013)
Hearing age is defined as a period of using any amplification. Most researches indicate that hearing age influences the developmental rate of auditory and speech-language abilities in deaf children, especially when cochlear implantation was performed before the age of three. This research is aimed at analyzing the influence of hearing age on understanding verbal instructions in children with cochlear implants. The sample consists of 23 children with cochlear implants and 21 children with normal hearing, aged between 4 and 10. Hearing age of children with cochlear implants was between 2 and 7 years. Token Test with toys, adapted for children with hearing impairments, was used to analyze understanding verbal instructions. The results indicate that there are statistically significant differences between children with cochlear implants and children with normal hearing, aged between 4 and 7, on all subtests and the total score regardless of the hearing age (sub1 p<0.001, sub2 p<0.000, sub3 p<0.001, total score p<0.000 ). No statistically significant differences were determined on any of the subtests in children aged between 7.1 and 10, regardless of the hearing age. Comparative results analysis within the experimental group of children with different hearing age indicates that the difference in understanding verbal instructions between these two groups is not statistically significant. Key words: cochlear implant, hearing age, understanding